An Electrochemical Determination of the Total Reducing Capacity of Wheat, Spelt, and Rye Breads - Danuta Zielińska; Henryk Zieliński; Mariusz Konrad Piskuła (MDPI AG, 2022)
The most interesting activities associated with bread components such as phenolic compounds, fibre, tocols, or newly formed compounds in the Maillard reaction, are their reducing properties responsible for the formation of the overall reducing capacity of bread. Among the electrochemical methods, the cyclic voltammetry (CV) technique has been recently adapted for this purpose. In this study, the application of the CV assay for the determination of the total reducing capacity of flours, doughs, and breads as well as their crumbs and crusts, originated from wheat, spelt, and rye formulated on white flours (extraction rate of 70%) and dark flours (extraction rate of 100%) and baked at 200 °C for 35 min and at 240 °C for 30 min was addressed. The reducing capacity of hydrophilic extracts from white flours and breads as well as their crumbs and crusts showed double values when compared to that of lipophilic ones whilst hydrophilic and lipophilic extracts from dark breads and their parts revealed comparable levels. The dark wheat, spelt, and rye breads showed an approximately threefold higher total reducing capacity than white breads. Baking at higher temperature slightly increased the total reducing capacity of breads and the highest value was found for dark rye bread as well as its crust baked at 240 °C for 30 min. The cyclic voltammetry methodology showed to be especially suitable for screening the bread technology and allows for obtaining rapid electrochemical profiles of bread samples.